Parenting Children in A Religious Perspective of Fishermen's Families In Sinjai, Indonesia: Structural Functionalism Approach - AB, Syamsuddin; Syam'un, Syam'un; Ilham, Muh.; Jasad, Usman; Rasyid, Idris (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Parents have an Islamic legal responsibility to raise children, which of course is carried out from conception to birth and school age, families living along the coast with fishermen status are responsible for making their children quality. This study aims to analyze and describe how fishing families, fathers, and mothers, have practiced Islamic parenting to form quality children. The research method used a qualitative-empirical approach analyzed using structural functionalism theory. The research stages explore the place that is the target of the research and then formulate theories that lead the researcher to look deeper into the problem being studied, the instruments in the researcher's own research because they are sensitive and react to environmental stimuli that are considered meaningful. The data collected is in a natural setting, it is expected that events will be experienced by individuals, the data collected is descriptive, in-depth interviews, documentation studies. The research results show that; The parenting pattern of fishing families is carried out during the conception period, namely; during pregnancy; When parents are pregnant with their child, they always control their words, behavior, honesty, and prayer before having sex. Birth period; Islamic preparation, welcoming with the call to azanand iqamat, salawat badar, aqiqah by giving a name according to Islamic recommendations. At school age, prepare for your child's needs and maintain interaction. From a structural functional perspective, the fishing community on the Sinjai coast carries out its function of caring for children by instilling religious values combined with cultural values.